Review of Electricity Markets for Smart Nano - Grids (2019)
(Eng) This article is focused in reviewing the electricity markets models and the smart nano - grids characteristics, making a study about the main aspects related, structure and integration. Previous investigations are discussed and fundamental ideas are develope d and explained, and finally variables and constraints are exposed for modelling the electricity market including the considerations for smart nano grids.